Routing drones with refuelling constraints - Tan, Lee Seng (Nanyang Technological University, 2023)
Using drones for inspection has many benefits to the users as the drones are able to reach areas that are dangerous for humans or hard to reach areas. This project aims to create an efficient shortest path algorithm that is able to route drones through a network of multiple target nodes and strategically positioned depot nodes that are capable of refueling the drone when the drone is low in fuel before allowing the drone to continue on its route.